Principal Component Analysis of Nutrient Content of Root and Tuber Crops of Nepal - Ojha, Pravin; Karki, Roman; Manandhar, Utshah; Gotame, Tek Prasad (Journal of Nepal Agricultural Research Council, 2024)
The research aimed to cluster the nutrient profile of six root and tuber crops including chayote root. Potato cv. Janakdev and Khumal Upahar (from Lalitpur) and cv. MS-42-3 (from Nuwakot); sweet potato cv. Suntale 1 and landraces Bensishar White and Kimichaur Seto (from Lalitpur); landrace of elephant foot yam and taro (from Pokhara); landrace of chayote root (from Dhankuta) and cassava (from Udaypur) were collected and Principal Component Analysis (PCA) was done based on their nutrient compositions. The evaluated nutrients included moisture, protein, fat, ash, crude fiber, carbohydrates, iron, calcium, phosphorus, sodium, potassium, zinc, vitamin C, and reducing sugar. PCA revealed that the first four principal components accounted for 85.7% of the total variation. Ash, calcium, and reducing sugar positively correlated with PC1 and PC2, while vitamin C, zinc, and protein were negatively associated with these components. There was a negative correlation of sodium concentration with potassium, phosphorus, and iron concentrations. Additionally, there was a negative correlation between carbohydrates and fat with the moisture content of the potatoes and tubers. The collected potatoes and tubers were classified into four clusters based on similarity and distance levels. The potatoes and sweet potatoes were placed in two distinct clusters. Elephant foot yam and chayote root were categorized in one cluster, distinguishing them from cassava. These findings highlighted the diverse nutritional profiles of the examined root and tuber crops, offering valuable insights for further research. Furthermore, the results can pave the way for commercial exploration of these potatoes and tubers based on their nutritional profiles.